Mewujudkan pendidikan berkualitas pasca pandemi Covid-19: praktek kepemimpinan digital dan kinerja tenaga pengajar - Lestari, Indah Ria; Rumangkit, Stefanus; Larasati, Hasna; Rahayu, Cindy (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
The Covid-19 pandemic has forced educational institutions to transform teaching through digital-based learning. This is a big challenge for educational institutions and the government in realizing quality education. The aim of this research is to analyze the application of visionary leadership, digital-based learning culture, digital citizenship, innovation skills, communication, digital leadership, digital-based knowledge sharing, and the performance of teaching staff in Indonesia. Primary data was obtained from the results of a questionnaire survey of 100 active teachers and lecturers spread across eight provinces in Indonesia. The survey was conducted directly and online using a quantitative approach and analyzed descriptively. The sampling technique was carried out using the convenience sampling method. The research results showed that the application of visionary leadership, digital-based learning culture, digital citizenship, innovation skills and communication in the workplace has gone well even though there are still a number of schools that do not have digital learning facilities. The strategy that schools and universities must implement to improve the performance of teaching staff in the digital era is to fulfill the physical and non-physical facilities in schools.